The bioethics of sexual practice in people with genetically transmissible physical handicaps - Baldacci, Maria Cristina (Medicina e Morale, 1997)
In most cases the corporality of handicapped people is relegated to simple re education and is mainly directed to better socialization. Erotic feelings are reduced to the spiritual area and are substituted by affection and platonic love as imposed by social ideologies. It is certainly much more difficult for an handicapped person to have an image of his body than for other people. His body is seen as a place of ambivalent feelings because it shows how he is different and also represents a part of him that does not respond to personal desires, neither functional nor in terms of relationships. Because of their disability physically handicapped people need appropriate help in enhancing their image. It is therefore necessary to help them discover "different beautiful" and gratifying aspects of themselves. Whithin this question, because of the moral problems involved, the author concentrates on genetically transmissible pathologies. In these cases it is necessary to let people understand the possibility of preventing higly probable, and maybe even certain, damage to a third person. In other words, according to the author, one has to collaborate with God in order not to generate pain, and the only way is through education. In fact it is to be hoped that a person with a pathology which is the sources of a genetically transmissible physical handicap will not practise his genital activity, but experience and "invent" the practice of his sexuality in a sublimated and trascendent way, keeping intact, and maybe even improving, his sexual and mental health.